CUX1, A Controversial Player in Tumor Development - Liu, Ning; Sun, Qiliang; Wan, Long; Wang, Xuan; Feng, Yu; Luo, Judong; Wu, Hailong (Frontiers in Oncology, 2020)
CUX1 belongs to the homeodomain transcription factor family and is evolutionarily and functionally conserved from Drosophila to humans. In addition to the involvement in various physiological events including tissue development, cell proliferation, differentiation and migration, and DNA damage response, CUX1 has been implicated in tumorigenesis. Interestingly, CUX1 has been recently recognized as a haploinsufficient tumor suppressor which is paradoxically overexpressed in tumor cells. While loss of heterozygosity and/or mutations of CUX1 have been frequently detected in many types of cancers, genomic amplification and overexpression of CUX1 have also been reported in cancer tissues and are correlated with higher tumor-grade and poor prognosis. Therefore, deciphering the roles of different CUX1 isoforms and in different tumor stages is required to establish a CUX1-based therapeutic strategy for cancer treatment.